“HOW THEY TEACH”: CASE STUDY JAVANESE LANGUAGE TEACHING IN THE COVID-19 CRISIS - Pudjastawa, Astrid Wangsagirindra (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
The purpose of this study was to identify the challenges experienced in the teaching and learning process of Javanese language for vocational students during the covid-19 period and to find out the strategies and solutions carried out during online learning. The method in this research is descriptive qualitative with a case study approach in Javanese language learning at voactional school in Malang Raya. The subjects in this study were 5 Javanese language teachers and 25 students. The findings indicate some challenges of learning Javanese, such as barriers in communication, low self-learning ability of students, and lack of control over students' morals and behaviour during distance learning. While the solution offered is technology-based learning as a learning material to improve the emotional relationship between students and teachers, reduce the level of difficulty, prioritize meaningful learning, and apply multi-literacy knowledge. While the techniques used are producing teacher laboratories, conducting self-assessments as a reflection of independent learning, and involving parents as substitutes for education instructors.